STUDENT READINESS HIGH SCHOOL ENTRANCE EXAMS HIGHER EDUCATION AND THE ROLE OF SCHOOL COUNSELORS - Anjar, Tri (Universitas Muhammadiyah Metro, 2015)
Abstract: The process of preparing to take the test SNMPTN is something that often makes prospective students experiencing various problems. I prepare for the selection of the necessary physical, material, and also psychological. This research was initiated from the problems that occurred in the preparation of the admission public universities by students coming from private schools . These problems such as high school rules violations / lack of discipline, learn less motivated to learn. This condition greatly affects the readiness of students to achieve success SNMPTN pass. This study aimed to describe the readiness of high school students college entrance exams and the role of BK teacher / school counselor. The study population is students of SMA Muhammadiyah 1 Metro are 212 students. This type of research is quantitative descriptive, and the questionnaire used as an instrument of collecting data. The results showed that the average score of 80.53 with an average percentage of 26.84%, are in the category is not ready. BK teacher's role in preparing students in private schools that help students related to school by making a counseling program, either individually or in the classical style. Increase cooperation with fellow teachers and parents and guardians to fostering the development of children's potential.Keywords: Readiness, Students, Counselor role